Pengaruh Waktu Perlakuan Kalium Permanganate (KMnO4) Terhadap Sifat Mekanik Komposit Serat Purun Tikus (Eleocharis Dulcis) - Kosjoko, Kosjoko; Sonief, Achmad As'ad; Sutikno, Djoko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
The combination between treatment time of the addition and directon fiber orientation wasused to get maximum mechanical properties of Purun Tikus fiber composites. The purpose ofthis study was to construct composite of polyester matrix and Purun tikus natural fiber by mixing2 % KMnO4 with 1 liter aquades for 15 minutes and 30 minutes. It is applied to determine tensile strength and flexural strength. The variation of volume fiber fraction are 20%, 30%, and 40%. The directon of Purun Tikus fiber are 0 and 90%, and the polyester matrix type 157 BTQN with1% concentration of MEXPO hardener. The dimension of tensile specimen refered to standart ASTM D638-03. The flexural strength was obtained trough bending test based on ASTM 790-03. The combination of these 2 variables can improve interfacial adhesion between fiber andmatrix. The highest tensile strength was 2% KMNO4 for 15 minutes of natural fiber composites Purun Tikus with volume 40@ about 55.54 N/mm2. The variation of 2% KMnO4 for 30 minutes the volume fraction of 40% was 41.07 N/mm2. The obtained of variation without KMnO4 treatment and fraction volume 40% about 40.03 N/mm2 The highest flexural strength of the composite fiber Purun tikus in the variation treatment 2% KMnO4 for 15 minutes with the volume fraction 40% was 119.70 N/mm2, for 30 minutes the fraction volume 40% was 80.88N/mm2, and the fraction volume 40% without treatment was 62.66 N/mm2.Keywords:purun tikus fibers, kalium permanganate, polyester, tensile strength & amp; flexuralstength